Significance of Faculty of Information Management in information management development in Malaysia / Nuramalina Syazwani Satmi - Satmi, Nuramalina Syazwani (Faculty of Information Management, 2015)
Nowadays, the need of employment is very important today. There are many employment opportunities created in the current era. Government and private sector itself has created to accommodate the latest post graduates who graduated from either public or private institutions. The academic program coupled repair by adding additional courses to provide a complete input by attached graduate training in the industry as one of the lessons. Graduates will be knowledgeable and skillful in the working world in the future and to overcome the challenges of managing information in various forms and in various organizations.